Female-headed households and the ultra poor in Bangladesh - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This report focuses on the magnitude of FHHs among the poorest and examines their socio-economic profile to highlight the distinction between FHHs and the entire sample. Female-headed households (FHHs) are of two types: households without any male adult where female is solely responsible for the well-being of the household and households where a female is the decision maker and receives monetary support from other male members who have migrated out for employment. The first one is defined as de facto and secone one as de jure households. The prevalence of FHHs among the ultra poor is calculated at 35%, of them 78% were de facto households. The de facto households were smaller in size, nearly SO% of them were comprised of one member households, 98% were single parent households, three-fourth of them were educationally dark, one-forth of them did not possess any living houses. One-third of the de facto household heads were either beggars or disabled. The de facto households were economically less well off. Major sources of their income were charity and wage employment. A lower percentage of the de facto households owned any kind of nonland assets, the value of which was also significantly lower than others. On the other hand, the de jure households were relatively more well-off compared to de facto households and on some indicator better-off than others.